Anticipating ageing: Older adults reading their medical records. Issue 3 (May 2018) - Huvila, Isto; Enwald, Heidi; Eriksson-Backa, Kristina; Hirvonen, Noora; Nguyen, Hai; Scandurra, Isabella
Highlights: Older adults, who are still active in working life but approaching retirement, differ from other age groups by their health information behaviour. Older adults are the least confident and least motivated to use online health information. Difficulties in understanding and accepting health information do not necessarily apply to medical records, i.e. health information about oneself. The results do not indicate an obvious linear relationship between age and motivation to use online health information. Personal health information management is a central aspect of health information behaviour. Abstract: In spite of the general interest in health information behaviour, there is little earlier research on how older adults, who are still active in working life but approaching retirement, differ from other age groups. A survey with Swedish patients who had ordered and read their medical record was conducted to map the preferences and motivations of older adults (born 1946–1960) ordering a copy of their medical record, and using medical records based e-health and information services in the future. The results do not indicate an obvious linear relationship between age and motivation to use online health information but show several differences between the age groups. Older adults were less interested in communication with their medical doctor by e-mail. Yet, they had searched health information in the Internet during the last week more likely than young. They were more inclined to read medical record to get an overview of their health than young, but less confident that they understood most of the content or turn to their family and friends to seek help than the elderly. When compared to younger adults and elderly people, older adults are the least confident and least motivated to use online health information. It is suggested that older adulthood can be seen as a transitory stage of life when the need of health information increases and engagement with health changes. The results agree with prior research on the potential usefulness of (online) medical records as a way to inform citizens. However, specific provision strategies may be necessary to match the needs and motivations of different age groups.